Another way of looking at the history of the wheel and technical aspect - Radkevych, A. V.; Bondarenko, L. M.; Yakovlev, S. O. (Science and Transport Progress, 2008)
The history of wheel in an initial period of its development from a viewpoint of physical possibilities of the animals domesticated by a man is traced. It is proved that coming from the last achievements of wheel age the history of humanity must be revised.